2013
DOI: 10.14214/sf.972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of picking methods on the berry production of bilberry (Vaccinium myrtillus), lingonberry (V. vitis-idaea) and crowberry (Empetrum nigrum ssp. hermaphroditum) in Northern Finland

Abstract: Effects of picking methods on the berry production of bilberry (Vaccinium myrtillus), lingonberry (V. vitis-idaea) and crowberry (Empetrum nigrum ssp. hermaphroditum) in Northern FinlandManninen O. H., Peltola R. (2013). Effects of picking methods on the berry production of bilberry (Vaccinium myrtillus), lingonberry (V. vitis-idaea) and crowberry (Empetrum nigrum ssp. hermaphroditum) in Northern Finland. Silva Fennica vol. 47 no. 3 article id 972. 12 p. Highlights• Berry production of bilberry, lingonberry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…This is probably because a biomass loss decreases the reproductive units of plants (Salemaa et al 1999) or reduces the size of bilberry (Strengbom et al 2003;Hegland et al 2005), which induces the need for an allocation of resources to a vegetative recovery instead of sexual reproduction. However, a delay in berry production was not detected in the study by Manninen and Peltola (2013), in which about 1% of bilberry biomass was lost after intentionally powerful picking by rake.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This is probably because a biomass loss decreases the reproductive units of plants (Salemaa et al 1999) or reduces the size of bilberry (Strengbom et al 2003;Hegland et al 2005), which induces the need for an allocation of resources to a vegetative recovery instead of sexual reproduction. However, a delay in berry production was not detected in the study by Manninen and Peltola (2013), in which about 1% of bilberry biomass was lost after intentionally powerful picking by rake.…”
Section: Discussionmentioning
confidence: 67%
“…Picking by plastic hand rake, commonly used in household and leisure picking, or picking by long-handed metal rake applied for more intensive purposes, did not diminish the bilberry fruit production in the following two years even when raking was applied intentionally by force (Manninen and Peltola 2013). However, in the study by Manninen and Peltola (2013), the picking treatment was applied only once which may not correspond to a practical utilization of wild berry yields, where the same areas may be under continuous picking pressure. In order to fill this gap in knowledge, we conducted an experiment to examine the effect of continuous bilberry picking on subsequent berry production.…”
Section: Introductionmentioning
confidence: 84%
“…The growing lingonberry market demand since the 1980's (Burt and Penhallegon 2003) favoured the development of V. vitis-idaea commercial plantations with selection and use of over twenty cultivars (Hjalmarsson and Ortis 2001;Debnath and McRae 2001;Penhallegon 2006). However, in Central and Northern Europe the most of lingonberries are still harvested in the wild (Seeland and Staniszewski 2007;Manninen and Peltola 2013).…”
Section: Introductionmentioning
confidence: 99%
“…in Poland (Zarzycki et al 2002), has been observed. At present not more than 10% of wild V. vitis-idaea resources are harvested in countries which are the main lingonberry producers and consumers (Manninen and Peltola 2013), and probably much less in the others, so overexploitation of wild populations is not the reason for decline of this species. Some studies show that the serious threat to Vaccinium species comes from the transformation of coniferous forest to mixed forests (Matuszkiewicz et al 2013;Turtiainen 2015;Woziwoda et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…in Poland (Zarzycki et al 2002), has been observed. At present not more than 10% of wild V. vitis-idaea resources are harvested in countries which are the main lingonberry producers and consumers (Manninen and Peltola 2013), and probably much less in the others, so overexploitation of wild populations is not the reason for decline of this species. Studies show that the serious threat to some Vaccinium species comes from the transformation of Scots pine forest to mixed forests (Matuszkiewicz et al 2013;Turtiainen 2015;Woziwoda et al 2019b).…”
Section: Introductionmentioning
confidence: 99%